(untitled) (Research, Society and Development, 2020)
This work verified the influence of climatic variables on the diametric increase of forest species Schinus terebinthifolius Raddi., Mimosa scabrella Benth. and Bauhinia forficata Link in a forest undergoing recovery in 2007, in Guarapuava, Paraná. 43 trees of the species S. terebinthifolius, 38 of the species M. scabrella and 30 of the species B. forficata were sampled. Two samples were taken from each tree, the growth rings were marked and measured with the Image J Software, the measurements were subjected to quality control with the Cofecha Software and the timelines generated with the Arstan Software. The climatic variables were evaporation, insolation, annual precipitation (mm), maximum, average and minimum temperature (ºC) and relative humidity, obtained for the period from 2007 to 2018, made available by the meteorological station of the Universidade Estadual do Centro-Oeste - UNICENTRO, Guarapuava - PR. Pearson’s Correlation, factor analysis and main components were used to verify the relationship between climatic variables and increment. The results showed a significant positive correlation of the increase in diameter of the species B. forficata and S. terebinthifolius with the variables evaporation, precipitation, maximum, average and minimum temperature and negative with the variables insolation and relative humidity. The species M. scabrella presented a significant positive correlation with the variables evaporation, precipitation and minimum temperature, and a negative one with the variables insolation and relative humidity and did not present a significant correlation with the variables maximum and average temperature. The characteristic years of high and low growth are the same for the three species, which showed a high correlation between chronologies and high sensitivity to climatic factors. The variables precipitation and temperature influenced the growth of the species. The average increase in diameter for M. scabrella was 1.51 cm.year-1, 1.09 cm.year-1 for S. terebinthifolius and 0.73 cm.year-1 for B. forficata. Due to the conditions of the study area due to anthropic actions, actions such as physical isolation are recommended, so that the maintenance of the natural ecological processes of the forest is favored. Studies on the dendrochronology of trees that were implanted in degraded environments and submitted to recovery are necessary to understand the relationship between the growth of forest species and climatic factors and its importance for the maintenance of ecological functions in the place.